The Virtue of Being Underestimated: A Note on Discriminatory Contracts in Hidden Information Models - Wendelin Schnedler (Institute for the Study of Labor (IZA), 2001)
A standard hidden information model is considered to study the influence of the a priori productivity distribution on the optimal contract. A priori more productive (hazard rate dominant) agents work less, enjoy lower rents, but generate a higher expected surplus.
Keywords: D82; J71; 330; Adverse selection; statistical discrimination; stochastic order relation; Adverse Selection; Agency Theory; Leistungsanreiz; Anreizvertrag; Arbeitsproduktivität; Stochastischer Prozess; Theorie